Corruption in the Department of Home Affairs as a threat to national security. - Mabeba, Bernard (My University, 2014)
ABSTRACT The high level of corruption in the Department of Home Affairs (DHA), constituting a threat to National Security (NS), indicates that there are challenges facing South Africa (SA). This study examines this issue by focusing on one dimension – i.e. the Late Registration of Births (LRB). This study explores corruption practices of some Home Affairs officials in helping citizens and foreigners to obtain birth certificates illegally via the LRB. The study further explores the implications that these corruption practices have for NS, due to improper movement control, as LRB could be used to fraudulently obtain documents that may be used by criminals or terrorist elements. The study also explores the key challenges posed by LRB. Judging from the interviews held, there is a need to institute proper management of systems and movement control. The outcome from the interviews with five members of DHA, confirms that there is lack of, or no link to, the monitoring of both foreigners and South Africans in terms of their movements. To institute movement control, what is required is a a linkage of systems between the civic section, which deals with LRB and immigration centres, in order to facilitate the monitoring of movements by both South Africans and foreigners. Literature indicates that there has been limited research conducted on the challenges facing LRB – hence the purpose of this research. The study investigates the reason for the lack of a collective approach to movement control by security agencies and other departments tasked to protect the South African identity, to prevent undocumented nationals from crossing the boarders into SA and illegally obtaining South African documentation via LRB. This research is qualitative in design and approach and explores the existing challenges broadly, by paying attention to factors that could destabilise and pose a threat to NS. This study recommends that the challenges faced by LRB, which are related to security loopholes, be identified in order to ensure that national, integrated movement control of both South Africans and foreigners is strengthened and that a working relationship between other departments, particularly those in the security cluster, is realised. In so doing, ways to promote, protect and strengthen cooperation within and between South African government departments are recommended. A culture of cooperation and resource-sharing, so that border and LRB security procedures are strengthened to ensure that security measures effectively detect, reduce and deter illegal migration, is one way of strengthening the working relationship between NS agencies and departments.
MM 2013
Keywords: Civil service -- Corrupt practices,National security,Public administration -- Corrupt practices .